2002
DOI: 10.1038/sj.bjc.6600448
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cytochrome P450 3A drug metabolism is reduced in cancer patients who have an acute-phase response

Abstract: Inflammatory disease states (infection, arthritis) are associated with reduced drug oxidation by the cytochrome P450 3A system. Many chemotherapy agents are metabolised through this pathway, and disease may therefore influence inter-individual differences in drug pharmacokinetics. The purpose of this study was to assess cytochrome P450 3A function in patients with advanced cancer, and its relation to the acute-phase response. We evaluated hepatic cytochrome P450 3A function in 40 patients with advanced cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
153
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 20 publications
10
153
3
1
Order By: Relevance
“…More recently, it has been reported that cytochrome P450 3A activity, the principal drug metabolising enzyme in a variety of chemotherapeutic agents, is compromised in advanced lung cancer patients with an elevated C-reactive protein concentration (Rivory et al, 2002;Slaviero et al, 2003). One might therefore postulate that the presence of a systemic inflammatory response would be associated with increased toxicity in patients receiving platinumbased chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that cytochrome P450 3A activity, the principal drug metabolising enzyme in a variety of chemotherapeutic agents, is compromised in advanced lung cancer patients with an elevated C-reactive protein concentration (Rivory et al, 2002;Slaviero et al, 2003). One might therefore postulate that the presence of a systemic inflammatory response would be associated with increased toxicity in patients receiving platinumbased chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely to be linked to increased toxicity in these patients. Therefore, it is of interest that the activity of the enzyme cytochrome P450 3A, involved in biotransformation of more than half of all drugs currently available, is compromised in patients with an elevated C-reactive protein concentration (Rivory et al, 2002;Slaviero et al, 2003). It may be that moderation of the systemic inflammatory response will reduce such toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…These factors can have an impact on drug disposition, resulting in either ineffective drug doses or excessive toxicity (Thummel and Wilkinson, 1998;Schuetz, 2004). This concept is supported by a study demonstrating that reductions in CYP3A4 activity in patients with advanced cancer were correlated to an increased plasma concentration of the inflammatory mediators interleukin (IL-)6 and C-reactive protein (CRP) (Rivory et al, 2002;Slaviero et al, 2003). This was associated with reduced clearance and increased toxicity from docetaxel, a well-characterised substrate for CYP3A4.…”
mentioning
confidence: 95%